Alternatively activated macrophages actively inhibit proliferation of peripheral blood lymphocytes and CD4+ T cells in vitro. - Schebesch, C (1997)
We compared the immunological functions of interferon-gamma (IFN-gamma)-induced, classically activated macrophages (caM phi) and of interleukin-4 (IL-4)- and glucocorticoid-induced, alternatively activated macrophages (aaM phi) in a human co-culture system in vitro. Proliferation of peripheral blood leucocytes (PBL) or CD4+ T cells mediated by optimal doses of phytohaemagglutinin (PHA) or concanavalin A (Con A) was only marginally influenced by caM phi, but was strongly inhibited by aaM phi. The degree of lymphocyte proliferation sustained in the presence of caM phi was gradually reduced in a dose-dependent fashion by the addition of aaM phi. Flow cytometric analysis revealed that expression of costimulatory molecules such as CD11a, CD40, CD54, CD58, CD80 and CD86 did not vary significantly between caM phi and aaM phi and was low for CD58, CD80 and CD86. As shown by reverse transcriptase-polymerase chain reaction (RT-PCR) analysis, IL-10 was expressed in caM phi, aaM phi and control macrophages; the level of expression of IL-10 was slightly enhanced in aaM phi. Neither neutralizing anti-IL-10 antibodies, indomethacin nor NG-monomethyl-L-arginine (NMMLA) was able to reverse aaM phi-mediated inhibition of lymphocyte proliferation. Of several agents interfering with various second messenger pathways, cAMP and the Ca(2+)-ionophore A23187 inhibited differentiation of cultured human monocytes into phenotypically mature aaM phi expressing MS-1 high molecular weight protein (MS-1-HMWP) and RM 3/1 antigen, and prevented the suppressive action of aaM phi on lymphocyte proliferation. In conclusion, these results who that aaM phi actively inhibit mitogen-mediated proliferation of PBL and CD4+ T cells independently of the expression of costimulatory molecules and of IL-10, NO or prostaglandin synthesis, and that inhibition of phenotypic differentiation of aaM phi is paralleled by a lack of functional maturation. Thus, fully matured aaM phi may be functional in down-regulating CD4+ T-cell-mediated immune reactions by an as yet unknown mechanism.